Characterization of emergent Avibacterium paragallinarum strains and the protection conferred by infectious coryza vaccines against them in China. (16th September 2019) - Xu, Yang; Cheng, Jinlong; Huang, Xiuying; Xu, Meiyu; Feng, Jinling; Liu, Changqing; Zhang, Guozhong
ABSTRACT: Infectious coryza (IC ), an acute respiratory disease of chickens, is caused by Avibacterium paragallinarum . Here, the current epidemiological status of IC was investigated in China over 5 yr (2013 to 2018). A total of 28 Av. paragallinarum field isolates were identified by PCR tests and by sequence analysis of the hemagglutinin gene. The pathogenicities of 4 field isolates, the efficacy of 2 commercial inactivated oil-emulsion IC vaccines and vaccines containing different Av. paragallinarum isolates were also evaluated. The PCRs revealed a high rate (51.5%) of sample positivity for Av. paragallinarum during 2013 to 2018. Phylogenetic analysis showed that most field strains fell into the same cluster and had a farther genetic relationship with the early isolates from China. Pathogenicity testing revealed that the Chinese Av. paragallinarum isolates were able to induce the typical clinical signs of IC; hence, they were clearly pathogenic to chickens. Vaccine efficacy tests revealed that the 2 commercial inactivated oil-emulsion IC vaccines we tested had low protection rates against 2 selected Av. paragallinarum isolates after a single immunization, whereas the inactivated vaccine containing the Av. paragallinarum BJ26 isolate generated a relatively high protection rate against the field isolates compared with other three tested vaccines. The results indicate that IC is currently prevalent in China, and that commercial vaccines have not counteracted its presence in this country.